Design of Friction, Morphology, Wetting, and Protein Affinity by Cellulose Blend Thin Film Composition - Czibula, Caterina; Teichert, Gundula; Nau, Maximilian; Hobisch, Mathias; Palasingh, Chonnipa; Biesalski, Markus; Spirk, Stefan; Teichert, Christian; Nypelö, Tiina (Frontiers in Chemistry, 2019)
Cellulose derivate phase separation in thin films was applied to generate patterned films with distinct surface morphology. Patterned polymer thin films are utilized in electronics, optics, and biotechnology but films based on bio-polymers are scarce. Film formation, roughness, wetting, and patterning are often investigated when it comes to characterization of the films. Frictional properties, on the other hand, have not been studied extensively. We extend the fundamental understanding of spin coated complex cellulose blend films via revealing their surface friction using Friction Force Microscopy (FFM). Two cellulose derivatives were transformed into two-phase blend films with one phase comprising trimethyl silyl cellulose (TMSC) regenerated to cellulose with hydroxyl groups exposed to the film surface. Adjusting the volume fraction of the spin coating solution resulted in variation of the surface fraction with the other, hydroxypropylcellulose stearate (HPCE) phase. The film morphology confirmed lateral and vertical separation and was translated into effective surface fraction. Phase separation as well as regeneration contributed to the surface morphology resulting in roughness variation of the blend films from 1.1 to 20.5 nm depending on the film composition. Friction analysis was successfully established, and then revealed that the friction coefficient of the films could be tuned and the blend films exhibited lowered friction force coefficient compared to the single-component films. Protein affinity of the films was investigated with bovine serum albumin (BSA) and depended mainly on the surface free energy (SFE) while no direct correlation with roughness or friction was found. BSA adsorption on film formed with 1:1 spinning solution volume ratio was an outlier and exhibited unexpected minimum in adsorption.